Analysis of vascular access in hemodialysis unit of a tertiary care hospital - Islam, Shoaib; Khalid, Syed Arsalan; Qureshi, Mamoon Akbar; Butt, Noman (Pakistan Journal of Kidney Diseases, 2021)
A well functioning vascular access (VA) remains a major obstacle in the management of patients with end-stage renal disease (ESRD) on maintenance hemodialysis (MHD). In a case series we analyzed 107 patients (68 males and 39 females) who had been on HD for a period ranging from 1 to 168 months. Their mean age was 50.44 years (range: 18 to 85 years). The study aimed at analyzing the VA, including the management of its complications. In 63 patients (59.8%), HD was initiated through a temporary catheter due to late detection of chronic kidney disease (CKD) and delayed referral and 43 (40.2%) started HD with AVF. 93.5% had AVF as their permanent VA. Total 64 (59.8%) complications occurred in 107 patients and the venous aneurysm was the most common complication (48.4%) followed by the VA thrombosis (34.3%). During mean 3.4 years, 75 (70.1%) patients underwent VA creation only once while 24 (22.4%) had to undergo twice and 8 (7.5%) were those who had to get it created more than twice. Only 2 (3%) of these patients underwent interventions for VA complications. Early detection of CKD and referral to a vascular surgeon and a multidisciplinary approach is required for creation and maintenance of VA.